LPI‐based cooperative tactic for satellite communication uplink signal accompanied by directed and power limited jamming - Fei Wang; Xiaoyan Huang; Yiyuan Chen; Chenguang Shi; Jun Chen (IET Signal Processing)
Abstract To protect the satellite communication uplink signal (SCUS) from being intercepted by an eavesdropper, this study proposes several tactics to ensure SCUS being in the low probability of intercept (LPI) state. First, based on the satellite link equation, an optimisation model for LPI SCUS is established with coding and synchronisation of symbol and carrier frequency. However, when the satellite is on the synchronisation orbit, the LPI model of SCUS is still very likely to be intercepted by an eavesdropper that might be close to the SCUS. Aiming at this problem, the second tactic is to mask LPI SCUS with directed and power limited jamming. The purpose of using directed and power limited jamming is to reduce direction‐finding accuracy of the eavesdropper, and to achieve the optimal LPI performance with the minimum radiation energy. The high‐order cumulate algorithm is used to predict the signal‐to‐noise ratio of mixed signal in the second tactic. The simulation results show that the model of LPI SCUS can effectively reduce the detection probability compared with the traditional satellite uplink signals, and the second tactic can effectively reduce the direction‐finding accuracy of the SCUS by the eavesdropper.